The Lost Steps in the History of Political Ideas of Modernity, is Interdisciplinarity Chimerical? - Fernández García, Eduardo (Historiografías, 2022)
The analysis of the political ideas that promoted Modernity in Hispanic kingdoms surpasses the tightness of a historiographical perspective, because it demands necessarily conceptual clarifications typical of political theory or philosophy, and of political science, excessively attached to the theoretical constructions, which can disregard a necessary contextualization. Beyond the confrontation between evental history and conceptual history, the reluctance of modernist historiography to accept ideology prior to contemporary era denote suspicion of truly multidisciplinary research. In this article is postulated the need to move from multidisciplinarity to interdisciplinarity in the History of Political Ideas. It is not about so much methodological changes as an authentic transformation of the epistemic bases of approach, mainly to the treatises of the 16th and 17th centuries. Consequently, it is necessary to ask about the performance and limits of interdisciplinarity and the priority of perspectives involved in each case, given the impossibility of absolutely balancing the historiographic and the political sciences. Keywords History of political thought, Modern Age, multidisciplinarity and interdisciplinarity, ideology, mental and imaginary representations